Demographic change and the European income distribution - Mathias Dolls; Karina Doorley; Alari Paulus; Hilmar Schneider; Eric Sommer (University of Essex, Institute for Social and Economic Research (ISER), 2018)
This paper assesses the effect of key demographic changes (population ageing and upskilling) that are expected by 2030 on the income distribution in the EU-27 and examines the potential of tax-benefit systems to counterbalance negative developments. Theory predicts that population ageing should increase income inequality, while the effect of up-skilling is more ambiguous. Tax-benefit systems may stabilize these expected changes though this is largely an empirical question given their typically complex nature. We use a decomposition technique to isolate the effect of projected demographic change on income inequality and poverty from the reaction of the labor market to this demographic change through wage adjustments. Our results show that demographic change is likely to lead to increasing inequality while related wage adjustments work mainly in the opposite direction. Changes to projected relative poverty are minimal for most countries. With a few exceptions, EU tax-benefit systems are able to absorb most of projected increase in market income inequality.
Keywords: J11; J21; J22; 330; income distribution; demography; labor market; decomposition